A Structural Equation Modelling of Organizational Culture and Total Quality Management at the Islamic University in Uganda (Sains Humanika, 2023)
This study aimed at examining the influence of organisational culture (OC) towards total quality management (TQM) at the Islamic University in Uganda. The study’s research Objectives were; examine whether the hypothesized model of organizational culture and total quality management fit the data. To establish whether the items for measuring organizational culture and Total quality management fit the model? To find out whether organizational culture construct statistically influence total quality management practices as perceived by staff at Islamic University in Uganda? To arrive at the intention of this study, a quantitative research design was employed, and a cross-sectional survey technique was used to attain data from 372 randomly chosen respondents. Data analysis was done using structural equation modelling. The findings of the study reflected that; the questionnaire items for OC and TQM fitted the data whereby CMIN was 1852.328, CMIN/DF 3.750, RMSEA .086, CFI .782 and DF 494.Further analysis to establish the influence of OC towards TQM reflected that CFI was .906, RMSEA .070, CMIN/DF 2.798, CMIN 506.362 AND DF 181; thus, the model fits the data. The influence of OC towards TQM was obtained at a .94 coefficient with a p-value of .000. The factor loadings for both constructs OC and TQM and their sub-constructs deemed reasonable at above 0.70. Thus, proving the model and theory worthy of employment in the management of HEIs so as to produce quality graduates with quality skills for addressing the 21st century challenges. More studies can be done using longitudinal surveys and other data analysis techniques to establish whether the results will differ. Lastly, it is recommended that leaders and their management teams in HEIs should change their perceptions towards running institutional businesses to fit the needs of the 21st century. Today’s world requires quality graduates with quality skills and culture to transform themselves and their community into a quality nation. However, these efforts cannot be achieved if HEIs leaders do not understand TQM’s meaning towards OC. This is because today's staff, students and other stakeholders are far different from the previous ones regarding their rights, services needed, input, the process and the output.
Keywords: Organizational Culture, Total Quality Management